Business Feasibility Study of Optical Permai Branch at Batam, Kepulauan Riau. - Prawiraningrum, Sandy Widya; Aliludin, Arson (The Indonesian Journal of Business Administration, 2014)
Abstract. Batam is one of the cities with rapid economic growth. Population growth in Batam also growing rapidly because many industries that established, so many business opportunities that are open to meet the needs of residents of Batam one of which is the need of glasses. Optical Permai is one of the older players on the field, but only has 2 stores in Jakarta. The owner saw a great opportunity to open a branch in Batam. There are several aspects that are used to analyze the business idea, the legal aspects, environmental aspects, the market and marketing, human resource aspects, technical and technological aspects, aspects of risk, and financial aspects. From the conclusion on an analysis of the business feasibility of Optical Permai Batam BranchÃ‚Â  showed that the establishment of a branch in Batam feasible in legal aspects, environmental aspects, the market and marketing, human resource aspects, technical aspects and technology, and financial aspects.Key words: business feasibility study, business development, legal aspect, environmental aspect, market and marketing aspect, technical and technology aspect, risk analysis, financial aspect.